PENGARUH KETERATURAN KONSUMSI TEH MANIS TERHADAPKELELAHAN PEKERJA (STUDI DI PABRIK TAHU ECO KELURAHAN JOMBLANG KECAMATAN CANDISARI KOTA SEMARANG) - Nur Zaini Rohman; Rahayu Astuti; Ulfa Nurullita (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background. The temperature of the working environment in the industry know very high ECObetween 36-500C such conditions can cause the appearance of sweat, the perspiration contained salt sodium chloride coming out along with the sweat that inhibits the transport of glucose in the body and cause the onset of muscle contraction. In the event of muscle contraction, the glycogen is converted into lactic acid that may hamper the work of muscles causing fatigue. With the granting of an additional drink regularly with carbohydrates very well to prevent the occurrence of fatigue caused by lack of fluids. Sweet tea is a drink containing carbohydrates are produced from the sugar content can be useful as an additional source of energy.. Purpose: To knowing the influence of granting sweet tea on a regular basis to the level of exhaustion factory worker knew ECO Village of Jomblang Sub-district Candisari Semarang. Methods: Type this research is specious experiment ( quasi experiment ) with delightful research before and after one group (one group before and after design). The variable independent granting tea sweetened and dependent variable the rate of fatigue work. Results: The rate of fatigue before work on the control group of 265.071 milli/sec and on the groups treatmen of 267.714 milli/sec. The rate of fatigue after work on control group of 407.062 milli/sec and on the groups treatmen of 220.062 milli/sec. The average rate of change fatigue in the control group of 2.643 milli/sec and average rate of change fatigue on the Group's treatment of -187.000 milli/sec to the value of p = 0.000 (p<0.05). Conclusion: There is a any influence granting tea sweetened the fatigue rate change.